If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + 6y + -8y = -3 + 3y Combine like terms: 6y + -8y = -2y 11 + -2y = -3 + 3y Solving 11 + -2y = -3 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 11 + -2y + -3y = -3 + 3y + -3y Combine like terms: -2y + -3y = -5y 11 + -5y = -3 + 3y + -3y Combine like terms: 3y + -3y = 0 11 + -5y = -3 + 0 11 + -5y = -3 Add '-11' to each side of the equation. 11 + -11 + -5y = -3 + -11 Combine like terms: 11 + -11 = 0 0 + -5y = -3 + -11 -5y = -3 + -11 Combine like terms: -3 + -11 = -14 -5y = -14 Divide each side by '-5'. y = 2.8 Simplifying y = 2.8
| 13x-4=7x-22 | | 48-32=4(12-x) | | -2gh(g^3h^5)=0 | | 7x+2=4x-9 | | 8b-8=-6(b-3)+6(1+2b) | | 12x-14=16x | | -(1+7x)-6(-7-x)=6 | | 7n-8+2+7n=0 | | -4(2+m)=2(m-7) | | 60y-108+12= | | Q+2=q+16 | | 12=1/3z+7 | | -4y^3-8xy^4=4y^3(1+2xy) | | 4y=5x+4 | | X-32=4(12-y) | | -6+4s=-2 | | 2u+4=16 | | 2(7x+3)=20 | | -2x+8x-7=6(x-4)-3 | | 0=3x^2-x-120 | | -6v+3v-9=-3 | | 4z+6=2z+6 | | -9=7(7v+8)+4(5v+1) | | 3(a-1)-5=34 | | 0.25(8z-4)=1z+8-2z | | 8-9+4b-5f= | | 4[5x-(2x-7)]=2(4x-5) | | 4k-13=11 | | 54=2x-9+4x | | 3(x+4)=2+3x | | 7-3r=r-8-4r | | 12-7(x-4)+x=-12 |